(untitled) (Nigerian Journal of Physiological Sciences, 2025)
ABSTRACT: The effects of various doses of Cymbopogon citratus (DC.) Stapf and Mangifera indica (L.) ethanolic leaf extract was investigated on fertility of male albino rats. Twenty-five (25) adult male rats were randomly grouped into five (5) cages (n=5). Control rats were given distilled water while experimental groups were daily administered ethanol leaf extract of C. citratus and M. indica through oral gavage at 150 and 300 mg/kg body weight, respectively; for 21 days. After the 21st day of post exposure (PE), experimental animals were sacrificed and their testes extracted and fixed. Sperm count, sperm morphology and sperm motility were assessed. C. citratus extract significantly increased mean sperm count of the treated rats at both 150 mg/kg body weight (272.00±7.47x106/ml) and 300 mg/kg body weight (297.00±3.62) groups, compared to those of M. indica extract (113.20±12.51x106/ml) and (27.60±3.67x106/ml) for 150 and 300 mg/kg body weight, respectively. Also, C. citratus produced a reduction in abnormal sperm morphology (15.20±1.77%) and (17.00±2.00%) for 300 and 150 mg/kg body weight, respectively; compared to M. indica extract (64.00±1.87%) and (51.00±3.32%) for 300 and 150 mg/kg body weight, respectively. M. indica significantly (p<0.05) reduced sperm motility while increasing sperm morphology indices of rats in all doses. However, C. citratus extract produced significant increase in sperm motility and a corresponding decrease in sperm morphology across the dose groups compared to M. indica extract. C. citratus boosted sperm count while M. indica decreased sperm count. The findings in this research indicated that C. citratus may influence fertility by stimulating sperm count production than M. indica, compared with control, and this effect is dose-dependent. Keywords: Cymbopogon citratus, Mangifera indica, human fertility control, contraceptives, family planning, sperm indices.